(3OjhGf cGXe GdCRQjs - (3GdGRQj , cGXe Hf eMeO Hf egOj Hf eQGO GdhGFdj GdHZOGOj,J (B1212 (3g` s
(3ChdgG (B:s
(3deYJ HQhbge Ydi GdOgfGA aGfMd YbO GdOeYI GdMeQGA s
(3BNQgG (B:s
(3ef bUjOI gGFjI WhjdI(B: (3Ej TF YHOJe EP YHSJe ef ojhqdj bqjeG Ydi PGJ Wg s
(3fSNI KGfjI eQJHIs
(3JQJjHkG gLGFjkG hHgG fbU ef bGajI GdTjf Edi bGajI GddGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B139s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B183 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs